Underlying Mechanisms of Biased Emotional Processing: The Influence of Emotional Intelligence and Nationality on Emotional Picture Processing - Spaltman, Mandy (Student Undergraduate Research E-journal!, 2016)
In many psychological disorders, one of the underlying issues is biased appraisal of emotional situations. In an attempt to unravel the underlying mechanisms of this phenomenon at a more fundamental level, the present study attempted to shed light on two individual characteristics, nationality and emotional intelligence, that may play a role in the processing of emotional pictures in three-dimensional emotion space. It was hypothesized that emotional intelligence and nationality would affect one’s rating of emotional images. However, results showed no effects of either. The search for mechanisms that result in biased emotional processing continues. Directions for future research are suggested.